2016
DOI: 10.2116/analsci.32.241
|View full text |Cite
|
Sign up to set email alerts
|

Visual Assay of Total Iron in Human Serum with Bathophenanthrolin Disulfonate-accommodated MCM-41

Abstract: A simple visual method for determining the total iron in human serum is proposed based on color development in the nanospace of mesoporous silica MCM-41 and a chromogenic ligand bathophenathroline disulfonate (BPS). Observing the color intensity of a complex between iron(II) and BPS devloped on the MCM-41 material by the naked eye enabled us to quntify iron(II) with a detection limit of 0.5 μM. The BPS-loaded MCM-41 was successfully applied for quantifying the total iron in human serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The speciation of iron (Fe(II)/Fe(III)) is quite important in numerous fields such as plant science, the environment, pharmaceutics, and biology, and an interested reader can find several applications in the international literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A screening of the recently published methods (2016 to date) revealed that the speciation of iron (and/or the determination of total iron) is based on more or less known red/ox pretreatment steps, followed by state-specific color-forming or fluorescent reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speciation of iron (Fe(II)/Fe(III)) is quite important in numerous fields such as plant science, the environment, pharmaceutics, and biology, and an interested reader can find several applications in the international literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A screening of the recently published methods (2016 to date) revealed that the speciation of iron (and/or the determination of total iron) is based on more or less known red/ox pretreatment steps, followed by state-specific color-forming or fluorescent reactions.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the principles of such procedures can be found in Table 1. As can be seen from the methods included in Table 1, they can be categorized into three main groups: (i) methods that are based on the reduction of Fe(III), typically by ascorbic acid or hydroxylamine [9,10,[12][13][14][15]17,19,20,24]; (ii) methods that are based on the oxidation of Fe(II) by H 2 O 2 [11,16,18]; and (iii) methods where both Fe(II) and Fe(III) interact with the selected probe, offering the possibility to perform total iron quantification in a single run (no speciation is reported though) [21][22][23]. Alternatively, a less-applied recent procedure is the column-based separation of Fe(II)/Fe(III) using cation exchange chromatography followed by compatible ICP detection [25].…”
Section: Introductionmentioning
confidence: 99%